Dance to the Music of Time Conducting for ballet - McCarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Conducting for ballet. Because the ballet conductor cannot rule by fiat, he must exercise instead a more persuasive power. Lambert opened windows on other worlds for an art form prone to introspection and preoccupation with technique. PALABRAS CLAVE: ballet conductors, music directors, Constant Lambert, Graham Bond, John Carewe, Philip Ellis, Barry Wordsworth, Jacques Lacombe, Andrea Quinn, Bernard Haitink, Antonio Pappano, Paul Hoskins.